The shoreline and morphological responses to storm event at Ras Al-Hekma sandy beaches - Mohamed A. Oraby; Ramy Y. Marmoush; Hesham M. El-Badry; Morad H. Abdelsalheen (Ain Shams Engineering Journal)
Considering the increasing frequency of storms in addition to the high economical value of potential investments in Ras Al-Hekma, Egypt, this study investigates the morphological responses of the coastline to extreme storm events. Numerical tools SWAN and XBeach models were applied to simulate storm waves and beach evolution respectively. The morphological model was calibrated against recent laboratory wave basin measurements. Results revealed that wave energy concentrates at the headland, causing significant erosion, while milder slopes in the embayment experience sediment accumulation. Quantitatively, the headland retreated by about 12 m, while the embayment advanced 25 m offshore. The study indicates substantial variations in sediment transport, with headlands facing erosion from cross-shore transports and embayments accumulating sediment due to southward alongshore currents. These findings emphasize the need for strategic coastal management to mitigate erosion and flooding risks and support sustainable development. This study provides significant insights for future infrastructure and development projects in the region.